Berlioz's orchestration treatise : a translation and commentary - Berlioz, Hector, 1803-1869 (Cambridge musical texts and monographs., 2002)
Berlioz's Orchestration Treatise is a classic textbook which has been used as a guide to orchestration and as a source book for the understanding both of Berlioz's music and of orchestral practice in the 19th century. This is the first new English translation of Berlioz's complete text since 1856, and it is accompanied throughout by Hugh Macdonald's extensive and authoritative commentary on the instruments of Berlioz's time and on his own orchestral practice, as revealed in his scores. It also includes extracts from Berlioz's writings on instruments in his Memoirs and in his many articles for the Parisian press. The Treatise has been highly valued both for its technical information about instruments but also for its poetic and visionary approach to the art of instrumentation. Berlioz was not only one of the great orchestrators of the nineteenth century, he was also the author with the clearest understanding of the art.--Publisher description.